The Correlation Between Physical Activity And Fasting Blood Glucose Levels Among Employees of Universitas Swadaya Gunung Jati: A Cross-Sectional Study - Siti Nida Nafisah Solih; Kati Sriwiyati; Irene Gunawan (International Journal of Health and Pharmaceutical (IJHP), 2026)
Elevated blood glucose is an early manifestation of metabolic imbalance that predisposes individuals to the development of diabetes mellitus. The International Diabetes Federation (IDF) reported in 2023 that diabetes affects around 537 million individuals globally, equivalent to nearly one in every ten adults. Engaging in physical activity contributes to improved insulin responsiveness and supports the reduction of circulating glucose concentrations. Considering the variability of physical activity among employees, it is necessary to investigate its relationship with fasting blood glucose levels. The objective of this study was to analyze the relationship between physical activity and fasting blood glucose among staff members at Universitas Swadaya Gunung Jati Cirebon. The study was conducted using a cross-sectional design involving 69 respondents selected with a non-probability quota sampling method. Physical activity was measured through the Global Physical Activity Quistionnaire (GPAQ) and fasting blood glucose were assessed using an EasyTouch glucometer. The Kolmogorov-Smirnov test was applied to assess normality and the results indicated that the data were not normally distributed; therefore, the data were analyzed using Spearman’s correlation test. Finding revealed that the median physical activity was 3600 METs, indicating high activity and median fasting blood glucose level was 104 mg/dL as prediabetes. Further analysis demonstrated a significant inverse relationship (p=0.003, r=-0.352) with weak correlation strength. Overall, the findings emphazise a significant correlation between physical activity and fasting blood glucose, where individuals with higher activity levels corresponding to decreased fasting glucose levels